2020
DOI: 10.3390/fluids5020041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxidation Degree of Graphene Oxide on the Shear Rheology of Poly(ethylene glycol) Suspensions

Abstract: This work studies the influence of the concentration and oxidation degree on the rheological behavior of graphene oxide (GO) nanosheets dispersed on polyethylene glycol (PEG). The rheological characterization was fulfilled in shear flow through rotational rheometry measurements, in steady, transient and oscillatory regimes. Graphene oxide was prepared by chemical exfoliation of graphite using the modified Hummers method. The morphological and structural characteristics originating from the synthesis were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Due to the hydrophilic feature of GO, [ 13 ] it presents higher chemical affinity with polar polymers. [ 17–21 ] Li et al [ 20 ] showed the influence of different oxidation degrees of GO on its structure and on the poly (vinyl alcohol)/graphene oxide (PVA/GO) composite properties. They observed that the higher the amount of oxidizing agent (KMnO 4 ) added to the synthesis of GO, the higher the oxidation degree of it.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydrophilic feature of GO, [ 13 ] it presents higher chemical affinity with polar polymers. [ 17–21 ] Li et al [ 20 ] showed the influence of different oxidation degrees of GO on its structure and on the poly (vinyl alcohol)/graphene oxide (PVA/GO) composite properties. They observed that the higher the amount of oxidizing agent (KMnO 4 ) added to the synthesis of GO, the higher the oxidation degree of it.…”
Section: Introductionmentioning
confidence: 99%
“…Hereσ [i] represents the decreasing order values ofσ for which a stable aligned solution is found. For the first value,σ = σ [1], we use the stable solution of a rigid undeformed body oriented at φ c as the initial guess, and for the second, and slightly reduced, valueσ [2], we use the final profile from the previous step as the initial guess. For the following steps, the last two profiles forσ [i − 1] andσ [i − 2] are used to approximate an initial guess of the profile for the givenσ [i].…”
Section: -6mentioning
confidence: 99%
“…In the particular case of 2D particle suspensions and molten composites, several works report either Newtonian or non-Newtonian flow behavior, thixotropicity, macroscale superlubricity, capability of forming particle network under shear flow, the presence of negative-to-positive normal stress first difference, and rheological responses similar to rod-like liquid crystal polymers as the main under-flow features [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Except for the work by Arapov and coworkers [ 22 ], the aforementioned studies have been carried out at a single temperature (room temperature in most cases) or within a small range of temperatures.…”
Section: Introductionmentioning
confidence: 99%